Black butler. 17 - Toboso, Yana, 1984- (Yen Press, Hachette Book Group, 2014)
"Due in no small part to Sebastian, his uncommon butler, Earl Ciel Phantomhive finally succeeds in earning an audience with the enigmatic headmaster of Weston College following the outcome of the annual cricket tourney. As moon-pale petals bloom on the lapels of the students who have been granted a place at the Midnight Tea Party, the man who holds all authority at the school reveals himself to his guests. Will his appearance shed light on the fate of the students who have gone missing, or will the mysteries continue to pile up within these hallowed school grounds?"--